Facebook as an Innovative Resource to Support Academic Processes in the Days of Covid-19: An Analysis the Use of Social Network in Baccalaureate - Henry Javier Zambrano Mendoza, Jeovanny Moisés Benavides Bailón, Maria Rodríguez Gámez (International Journal of Advanced Science and Technology, 2020)
Given the situation facing the world due to the Covic-19 pandemic, they have raised alternatives to continue with the educational processes using ICT and e-learning as an academic resource, a range of software and applications were implemented by institutional managers as an alternative to the teaching-learning process; Faced with the health emergency, there are drawbacks when not knowing the technological handling of the tools by teachers and students. The objective of the research is based on analyzing the use of the Facebook application as an innovative resource to support academic processes at the time of Covid-19 within the baccalaureate level. Bibliographic, inductive-deductive and online survey methods were applied, which reflected that teachers have knowledge of various technological applications with an educational focus, however, students have a higher degree of knowledge in applications such as WhatsApp and Facebook. This provided a favorable approach to apply the social network Facebook within educational activities due to the high percentage of accessibility that this application has among members of the educational community.